Well Performance Simulation and Parametric Study for Different Refracturing Scenarios in Shale Reservoir - Jing Huang; Lan Ren; Jinzhou Zhao; Zhiqiang Li; Junli Wang (Geofluids)
Refracturing is an encouraging way to uplift gas flow rate and ultimate gas recovery from shale gas wells. A numerical model, considering the stimulated reservoir volume and multiscale gas transport, is applied to simulate the gas production from a refractured shale gas well. The model is verified against field data from a shale gas reservoir in Sichuan Basin. Two refracturing scenarios: refracturing through existing perforation clusters and refracturing through new perforation zones, are included in the simulation work. Three years after production is determined to be the optimum time for refracturing based on the evolution analysis of reservoir pressure, effective stress, fracture permeability, and gas recovery. The role that the hydraulic fracture conductivity and hydraulic fracture half-length play in gas production for different refracturing cases is explored. Pumping parameters of the refracturing job in Sichuan Basin are discussed combining with sensitivity analysis, and suggestions for pumping parameters optimization are proposed.